Managing Mortality: Key Factors Influencing Hemiarthroplasty Outcomes in Geriatric Patients with Proximal Femur Fractures - Ercan Bayar; Tolgahan Cengiz; Şafak Aydın Şimşek; Bedirhan Albayrak; İsmail Büyükceran; Yılmaz Tomak (Medicina)
Background and Objectives: Proximal femur fractures represent a significant health issue in the elderly, associated with high morbidity and mortality rates. This retrospective cohort study investigated factors influencing mortality (age, gender, infection, mobilization status, hospital stay length, surgical delay) in patients undergoing hemiarthroplasty for proximal femur fractures in a tertiary university hospital in Turkey. Materials and Methods: A retrospective analysis was conducted on 481 patients who underwent hemiarthroplasty at 19 Mayıs University hospital in Turkey between 2012 and 2022, with final follow-up data collected in 2022. Data collected included demographic information, the type of surgical approach, the duration of surgery, comorbidities, postoperative complications, and mobilization status at 1 and 6 months post-surgery. Statistical analyses were performed using the Mann–Whitney U test for age and surgery delay; the Kruskal–Wallis test for comparisons of mortality subgroups; the Chi-square test for categorical variables such as gender, fracture type, anesthesia type, and postoperative complications; and the Z test for post hoc analysis of categorical data. Results: The overall mortality rate at final follow-up was 56.1% over the entire study period (2012–2022), with a 6-month mortality rate of 21.8% and a 1-year mortality rate of 33.2%. Age and male gender were significant predictors of mortality. Infection rates were significantly associated with higher mortality within the first year. The study found no significant relationship between surgical approach, duration of surgery, or anesthesia type and mortality. However, increased length of hospital stay and delayed surgery correlated with higher mortality rates. Mobilization status significantly impacted survival, with immobilized patients demonstrating the highest mortality rates. Conclusions: Mortality following hemiarthroplasty for proximal femur fractures is influenced by various factors, including age, comorbidities, infection, and mobilization status. Implementing strategies for early surgery and mobilization while maintaining strict aseptic techniques could potentially reduce mortality rates in this high-risk population.